ショウワキチ ニ オケル タイキ デンキ ノ カンソク 1969 1970 - 近藤, 五郎; コンドウ, ゴロウ; KONDO, Goro (国立極地研究所, 1971)
P(論文) As a part of meteorological research programmes of the 10th Japanese Antarctic Research Expedition, atmospheric-electric observations of electric field, conductivity, and air-earth current near the surface at Syowa Station wefe carried out Continuously from February 1969 to January 1970, in concert with the measurements of vertical distribution of electric potential gradient by releasing special electric radiosondes. The annual mean value of electric field was 66V/m, conductivity 2.91 × 10^<-14> mho/m, air-earth current 1.56 × 10^<-12> A/m, and the vertical distribution of potential gradient (V/m) was expressed by the following empirical equation : E=E_0 exp (-0.29h), where h is the height (km). The mean diurnal variations of electric field and air-earth current were not much different from those in the worldwide thunderstrom activities. departmental bulletin paper